2018
DOI: 10.1177/2041669517747297
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Common Summary Statistical Process for Representing the Mean and Variance? A Study Using Illustrations of Familiar Items

Abstract: A number of studies revealed that our visual system can extract different types of summary statistics, such as the mean and variance, from sets of items. Although the extraction of such summary statistics has been studied well in isolation, the relationship between these statistics remains unclear. In this study, we explored this issue using an individual differences approach. Observers viewed illustrations of strawberries and lollypops varying in size or orientation and performed four tasks in a within-subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 40 publications
5
30
1
2
Order By: Relevance
“…Only few studies have addressed one or both of these questions. In one such study, Yang, Tokita, and Ishiguchi (2018) demonstrated the lack of correlation between the perception of mean and the perception of variance. This suggests that these two statistics can be computed quite independently, even when applied to the same domain (size or orientation).…”
Section: The Functional Architecture Of Ensemble Perceptionmentioning
confidence: 99%
See 3 more Smart Citations
“…Only few studies have addressed one or both of these questions. In one such study, Yang, Tokita, and Ishiguchi (2018) demonstrated the lack of correlation between the perception of mean and the perception of variance. This suggests that these two statistics can be computed quite independently, even when applied to the same domain (size or orientation).…”
Section: The Functional Architecture Of Ensemble Perceptionmentioning
confidence: 99%
“…Although testing the perception of two statistics in a single precue/postcue task (Utochkin & Vostrikov, 2017) is advantageous over separate tasks (Haberman, Brady, & Alvarez, 2015;Lee et al, 2016;Yang et al, 2018) in terms of its capability to probe parallelism along with independence, an important methodological caveat can be put forward. Specifically, when a correlation between tests is estimated across participants, each data point represents an average score that does not take into account what happens in particular trials.…”
Section: Our Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, participants' reports of variability were also more accurate than one would expect based on their reports of mean size in a previous experiment. Solomon et al (2011) suggested that this is accounted for by some form of late decision noise in the computation of mean size, but an alternative suggestion is that participants simply use different cognitive strategies in computing the two (e.g., Yang, Tokita, & Ishiguchi, 2018).…”
Section: Existing Evidence About Variability Discriminationmentioning
confidence: 99%